Unveiling spatial and temporal patterns of second home dynamics: a Bayesian spatiotemporal analysis for a Mediterranean island. Issue 1 (2nd January 2022) - Yuheng, Ling; Detotto, Claudio; Prunetti, Dominique; Stein, Alfred
ABSTRACT: The second home is an important issue for a housing market and has effects on local land use. Conventional approaches do not consider second homes varying across space and time. Hence, spatial models, such as the Besag, York and Mollie (BYM) model and its variants, offer a feasible way to model both covariates and spatial, temporal dependence. This model is applied in our study to analyse the second home incidence rate at a county level in Corsica, France, over the period 2006–16. We investigate the spatially referenced covariates and localize 'hot spots' of the incidence rate across Corsican counties. Further, the temporally structured component reveals that there was a gradual increase in the incidence rate over the period under study.